1181. Predictive Score for Dengue Infection with Complete Blood Count Parameters, Including the New Monocyte Distribution Width – a Retrospective Single Center Derivation and Validation Study. (15th December 2022) - Phuttasen, Naiyana; Pornprasitsaeng, Surapong; Onthong, Yupapin; Sinthana, Thurdsak; Limvorapitak, Wasithep
Abstract: Background: Dengue infection is a differential diagnosis in patients with acute undifferentiated fever. Early detection and management may reduce mortality. Monocyte distribution width (MDW) is a new parameter in complete blood count (CBC). It is recently approved for early detection of sepsis. We have noticed high MDW in Dengue patients. This study aimed to describe MDW changes in Dengue infection and to develop predictive score for early detection of Dengue infected patients. Methods: We retrospectively retrieved data of adult patients with acute fever who had CBC and Dengue serology (NS1 antigen, IgM and IgG) performed during September 2019 to May 2020 at Thammasat University Hospital. Medical records were reviewed. MDW was compared between groups. Patients were randomly divided into training and validation set. Predictive score was developed from the training set and validated in the validation set with multivariable analysis. Results: A total of 431 patients, with Dengue infection in 127 patients (29.5%), were included in the analyses. The median (interquartile range) of MDW in Dengue patients were higher than non-Dengue patients [29.7% (26.5 – 34.7) vs. 24.2% (21.1 – 27.8), P < 0.001]. In patients with confirmed Dengue infection, MDW increased with increasing severity (Figure). Training and validation sets included 216 and 215 patients with 64 and 63 Dengue infection, respectively. Independent predictive factors of Dengue infection were white blood cell < 4 x 10 9 /L (score 1), platelet < 100 x 10 9 /L (score 1) and MDW > 24% (score 1). No clinical features were independently predictive of Dengue infection. The area under receiver-operating-characteristic curve (95% confidence interval) of the prognostic score in the training and validation set were 0.839 (0.779 – 0.899) and 0.742 (0.674 – 0.811), respectively. With the cut-off score ≥ 1, the sensitivity and specificity of the score were 92.2% and 40.8% in the training set and 88.9% and 44.1% in the validation set. Monocyte distribution width in Dengue and non-Dengue patients Box-plot showing monocyte distribution width in patients with Dengue in comparison with non-Dengue (panel A) and compared between each Dengue severity (panel B) Conclusion: MDW increase in patients with Dengue infection and also increase with Dengue severity. We have developed and internally validated a simple predictive score for Dengue infection based on only results from CBC and MDW. Further large-scale external validation study is required to confirm the utility of our predictive score. Disclosures: All Authors : No reported disclosures.